Attitudes, Practices, and Barriers of Malaysian Community Pharmacists Toward Provision of Weight Management Services - Verma, Rohit Kumar; Paraidathathu, Thomas; Taha, Nur Akmar; Chong, Wei Wen (Frontiers in Pharmacology, 2019)
In Malaysia, sharp increment in the prevalence of obesity over the last four decades has been documented. Community pharmacists (CPs) are strategically placed to tackle obesity by providing weight managements services (WMS) to general public. This study assessed the attitudes, practices and perceived barriers of Malaysian CPs to the provision of WMS. A cross-sectional, descriptive survey was conducted, and responses related to attitudes, practices and perceived barriers of CPs were collected using five-point Likert scale. A total of 550 pharmacists who worked across six states of Malaysia (Selangor, Federal Territory of Kuala-Lumpur, Pulau Pinang, Johor, Sabah, and Melaka) participated in this study. Most of the CPs strongly agreed that over eating (n=312, 56.7%) and sedentary lifestyles (n=297, 54.0%) contribute to obesity and overweight. Most of them also strongly agreed that exercise training is an effective weight reduction strategy (n=25, 51.8%), but they were generally not in favor of surgery (n=231, 42% disagreed/strongly disagreed). CPs generally perceived barriers related to a lack of staff to provide WMS (n=308, 56.0% agreed/strongly agreed) and ethical and legal issues associated with sales of products/drugs for obesity management (n=285, 51.9% agreed/strongly agreed). Sociodemographic and practice characteristics such as age group, type of pharmacy, highest education qualification, and employment status of CPs influenced the attitudes, practices and perceived barriers associated with WMS. In terms of age, it was observed that CPs between 41-50 years old expressed significantly stronger agreement that medication adherence is beneficial for weight loss compared to those less than 30 years of age. Additionally, CPs who were pharmacy owners provided significantly more frequent BMI measurement and patient information materials as part of their weight management practices compared to CPs who worked as a part timer/locum. This study could be taken as a baseline study on Malaysian CPs’ perceptions on WMS. In terms of age, we observed that CPs between 41-50 years old expressed significantly stronger agreement that medication adherence is beneficial for weight loss compared to those less than 30 years of age. Future studies could focus on the perception of Malaysian general public towards the delivery of WMS in community pharmacy.